'Blest' or 't'othered': Alternative Graveyards in Bleak House, Reynolds, and Walker. (November 2018) - Doherty, Ruth
Abstract : This article proposes an alternative reading of Charles Dickens's Bleak House (1852–3), by attempting to recreate the reading experience of the first audience of this now well-studied novel. A comparison is made between key scenes in Bleak House and similar scenes in the first volume of George William Macarthur Reynolds's The Mysteries of London (1844), to demonstrate the differing literary styles of these two popular writers. The article draws on contemporary non-fiction, including George Alfred Walker's Gatherings from Grave Yards (1839) and several news articles, as well as more recent scholarship on Dickens to place the representations of graveyards in the novels of Reynolds and Dickens within the larger discussion of the necessity of sanitary reform in London at the time. The article argues that a proper consideration of this context enriches our understanding of the thematic structure of Bleak House .